Teachers’ perception of the necessity of applying online applications for organizing teaching activities at high school in Vietnam - Le, Thang Van; Nguyen, Ha Le; Nguyen, Hung Thanh (Journal of Education and e-Learning Research, 2023)
E-learning has gained popularity as a method of delivering education recently and offers many advantages to enhance the learning experience for students. Technology allows teachers to design more interactive and engaging lessons that cater to different learning styles. It can also provide opportunities for teachers to incorporate virtual simulations and real-time data which can help students better understand complex concepts. The total number of survey samples was 187 teachers. Awareness of the need and purpose of applying information literacy in the organization of teaching activities was created to analyze. The results of the findings were interpreted in three ways: (i) Self-assessment of teachers’ competence in applying technology in organizing teaching activities. (ii) Awareness of the necessity of using online applications in organizing teaching activities in schools. (iii) Awareness of the goal of using online applications in the organization of teaching activities. Based on the results of the current study, the article establishes the process of applying online applications in the organization of teaching activities and proposes recommendations for subjects directly related to the application of online applications. High school administrators, teachers and educational management agencies at all levels are using online innovation to organize teaching activities in high schools.